An L-shaped ultrasonic linear piezoelectric motor with two second-order bending coupling modes. (17th February 2018) - Chu, Xiangcheng; Gao, Shuning; Zhang, Mengfan; Zhong, Zuojin; Zhao, Yanqiang; Yuan, Songmei; Li, Longtu
ABSTRACT: In order to simplify the motor structure, reduce the difficulty of modal coupling and obtain a wide driving frequency range, a new piezoelectric motor which works on the two second bending vibration coupling modes was designed in this study. Based on the bonded-type structure, it consists of four pieces of piezoelectric ceramics, a copper substrate and one driving tip. The finite element method (FEM) was used for optimizing the design and further analysis, and a prototype was designed, fabricated and experimentally researched in this study for verifying its mechanical properties. Experimental results show that the working frequency is 89 kHz, and the maximum value of the movement velocity of a certain direction is 53 mm/s, at 680 Vpp (voltage, peak to peak value), while the maximum movement velocity of reverse direction is 44 mm/s at the same voltage.